Project Based Learning: Strategi Efektif Untuk Meningkatkan Creative Thinking Ability - Jusmardi, Jusmardi; Darwin, Widya; kurniawan, Ade; Deswina, Melri; Febrianti, Novi (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
In the era of globalization and technological developments, students are required to have critical thinking skills and competencies, problem solving skills and the ability to think creatively. This article discusses the application of Project-Based Learning as an effective strategy in improving students' creative thinking abilities in the Network Systems Administration course, even semester January-June 2023, Padang State University's Informatics Engineering study program. The research design used was Quasi Experimental, involving two class groups, each an experimental class and a control class. This research produced findings that showed significant differences in increasing creative thinking skills between the experimental class and the control class. This difference can be seen from the results of the N-gain test (0.006 < 0.05), which shows that the average increase in creative thinking skills in the experimental class is higher than in the control class. Analysis per indicator shows that the increase in N-gain in the experimental class in the Fluence and Flexibility indicators is in the high category, while the Originality and Elaboration indicators are in the medium category. This finding is supported by the higher level of learning activity in experimental class students compared to the control class. Apart from that, positive responses from students regarding the implementation of the project based learning model can also be seen from the results of the questionnaire instrument.Keywords: Network System Administration, Creative Thinking Ability, Project-Based Learning